2000
DOI: 10.1093/geront/40.5.568
|View full text |Cite
|
Sign up to set email alerts
|

Does Type of Disease Matter? Gender Differences Among Alzheimer's and Parkinson's Disease Spouse Caregivers

Abstract: Loss of reciprocity in marital relationships may affect women more negatively than men. Future studies that address underlying mechanisms of gender differences and focus on similar caregiving situations and contexts deserve attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 33 publications
5
81
1
1
Order By: Relevance
“…Similar to Carter et al (2008), this study indicated that being older, married, a man, employed irrespective of caregiving task decreased the likelihood of suffering from a depressive disorder. In accordance with previous research, females had an increased risk of suffering from a depressive disorder in comparison to men (Greenberg et al, 1993;Hooker et al, 2000;Schulz et al, 2009). Previous research has shown that women are nearly twice as likely to suffer from depression as men (Schulz et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to Carter et al (2008), this study indicated that being older, married, a man, employed irrespective of caregiving task decreased the likelihood of suffering from a depressive disorder. In accordance with previous research, females had an increased risk of suffering from a depressive disorder in comparison to men (Greenberg et al, 1993;Hooker et al, 2000;Schulz et al, 2009). Previous research has shown that women are nearly twice as likely to suffer from depression as men (Schulz et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…For example, women are more likely to have to contend with balancing work and looking after children which could increase stress levels and make them more vulnerable to developing depression (Pruchno et al, 1990;Schulz et al, 2009). Women may be more likely to report symptoms of depression where men due to stigma may underreport symptoms or not recognise symptoms of depression (Hooker et al, 2000). Therefore, the gender differences found in this study could be influenced by increased stressors and the reporting of symptoms.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…[5][6] In addition, when women are solely responsible for caring, they may experience feelings of guilt over not caring enough. 7 In one study, the authors reported that female caregivers and young adults in general reported having had more negative experiences related to care than male caregivers and spouses, respectively. 8 Caring wives were the least likely to report positive experiences deriving from care.…”
Section: Family Caregivers From the Perspective Of Roy's Adaptation Mmentioning
confidence: 99%
“…26 Supporting these findings, other authors found that caregivers who took care of children while taking care of relatives with cancer were particularly prone to experience psychological distress and greater difficulty in finding meaning in the role of caregiver for a person with cancer. 7 The environmental stimuli of the family caregiver are processed by the regulatory and cognitive subsystems that act in the adaptive modes. It is emphasized that the regulatory subsystem is particularly relevant in family caregivers, as the continuous exposure to stimuli that require adaptation may activate mechanisms that involve the deregulation of the neuroendocrine-immunological axis, including the autonomic nervous system and the hypothalamic-pituitary-adrenal axis, leading to the deregulation or deterioration of organic functions.…”
Section: Family Caregivers From the Perspective Of Roy's Adaptation Mmentioning
confidence: 99%